Sex Hormones and Immune Dimorphism - Aruna Bhatia; Harmandeep Kaur Sekhon; Gurpreet Kaur (The Scientific World Journal)
The functioning of the immune system of the body is regulated by many factors. The abnormal regulation of the immune system may result in some pathological conditions. Sex hormones of reproductive system are one of the major factors that regulate immune system due to the presence of hormone receptors on immune cells. The interaction of sex hormones and immune cells through the receptors on these cells effect the release of cytokines which determines the proliferation, differentiation, and maturation of different types of immunocytes and as a result the outcome of inflammatory or autoimmune diseases. The different regulations of sex hormones in both sexes result in immune dimorphism. In this review article the mechanism of regulation of immune system in different sexes and its impact are discussed.